Simplification of the Scamper model for development of creative images in advertising - Marugán Solís, Fernando (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The technique called SCAMPER is still one of the most used, both in advertising and in teaching, for the development and creation of ideas and creative images. Its name is an acronym that refers to six techniques: substitute, combine, adjust, modify, put to other uses, eliminate & reverse. This article proposes to simplify the processes formulated in this technique, reducing them to four processes, and for thest udy developed in this article, award-winning graphic advertisements at Advertising Creativity Festivals. Finally, the article also develops a classification of these techniques.